Knowledge of HIV/AIDS and its determinants in India: Findings from the National Family Health Survey-5 (2019–2021) - Mansi Malik; Siaa Girotra; Debolina Roy; Saurav Basu (Population Medicine)
Introduction HIV is a chronic viral infection that invariably progresses into a life-threatening condition known as AIDS. India has the third highest burden of HIV in the world with an estimated 2.3 million people living with HIV (PLHIV) in 2021. Existing studies assessing the knowledge and attitude towards HIV/AIDS in India have small sample sizes with regional bias and lack of representativeness. Thus, the study objective was to determine the proportion and predictors of knowledge and attitude of HIV/AIDS in the Indian population through a large, nationally representative demographic and health survey (DHS).